2020
DOI: 10.1029/2019gl084206
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Active Kelvin–Helmholtz Vortices on Saturn's Magnetopause Boundary

Abstract: For ∼2,000 Cassini magnetopause encounters, we analyse plasma and magnetic fields. The boundary can be unstable to the Kelvin–Helmholtz instability (KHI), which can drive large‐scale flows identifiable in plasma measurements. Bulk flow reversed from the expected direction near the magnetopause can indicate vorticity associated with active KH, and events are found dominantly in the dawn–subsolar region. KHIs are also responsible for magnetic field fluctuations, and hybrid simulations indicate heating, and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…(2021) and Burkholder et al. (2020) show that heating rate densities ∼10 −15 W/m 3 occur roughly 5% of the time based on the Cassini magnetometer data. Integrating 10 −15 W/m 3 over 5% of the magnetodisc volume yields a power input ∼200 GW, consistent with empirical estimates by Bagenal and Delamere (2011).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…(2021) and Burkholder et al. (2020) show that heating rate densities ∼10 −15 W/m 3 occur roughly 5% of the time based on the Cassini magnetometer data. Integrating 10 −15 W/m 3 over 5% of the magnetodisc volume yields a power input ∼200 GW, consistent with empirical estimates by Bagenal and Delamere (2011).…”
Section: Resultsmentioning
confidence: 94%
“…10.1029/2020JA028479 2 of 11 (Burkholder et al, 2020). KH activity is expected in the prenoon sector where the fluctuations maximize.…”
Section: Turbulent Heating Estimatementioning
confidence: 99%
“…be associated with the growth and evolution of Kelvin-Helmholtz vortices on the magnetopause boundary and these vortices are independent of IMF orientation. Burkholder et al (2020) studied the heating rate density of the quiet and the disturbed events using the similar analysis at the magnetopause boundary. They showed that the heating rate density of the disturbed events is two orders of magnitude greater than the quiet events which is similar to our result.…”
Section: -15mentioning
confidence: 99%
“…This patchy network of disturbed events could be responsible for spot heating in the magnetosphere. Burkholder et al (2020) assumed that plasma parcels near the subsolar magnetopause boundary take ∼6 h before being swept down tail to exit the magnetosphere. Given q ∼ 10 −15 W m −3 for 6 h, the plasma temperature can change by 100's of electronvolt for average Saturn parameters.…”
Section: Turbulent Heatingmentioning
confidence: 99%
“…Other patterns of detections exist in this dataset, namely the extremely high and low latitude detections of 2007, mid 2009, 2013, and 2014. Identifications at these latitudes are due to the highly angled orbital trajectory of Cassini at these times (see Figure 2), where it comes close to the magnetopause boundary and hence may identify Kelvin-Helmholtz (K-H) instabilities in magnetic field observations (Delamere et al, 2013b;Johnson et al, 2014;B. L. Burkholder et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%